1998
DOI: 10.2337/diabetes.47.4.550
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin directly triggers GLUT4 translocation via an insulin-independent pathway.

Abstract: Physical exercise induces translocation of GLUT4 from an intracellular pool to the cell surface in skeletal muscles and increases glucose uptake via an insulin-independent pathway. However, the molecular mechanism remains to be identified. Some studies have suggested that bradykinin is locally released from contracting muscles and may be responsible for GLUT4 translocation and the increase of glucose transport in skeletal muscles. To determine whether bradykinin directly triggers GLUT4 translocation, we establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 0 publications
2
109
0
3
Order By: Relevance
“…While the insulin pathway involves insulin binding to its receptor inducing tyrosine kinase activity, phosphorylation of insulin receptor substrate proteins with subsequent activation of phosphatidylinositol-3-kinase [6], the contraction pathway, is independent of these steps [7][8][9]. A number of molecules including calcium [5,10], protein kinase C [5], AMP-activated protein kinase (AMPK) [11], bradykinin [12] and NO [13] have been implicated in contractionmediated glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…While the insulin pathway involves insulin binding to its receptor inducing tyrosine kinase activity, phosphorylation of insulin receptor substrate proteins with subsequent activation of phosphatidylinositol-3-kinase [6], the contraction pathway, is independent of these steps [7][8][9]. A number of molecules including calcium [5,10], protein kinase C [5], AMP-activated protein kinase (AMPK) [11], bradykinin [12] and NO [13] have been implicated in contractionmediated glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, studies in vitro showed that isolated rat muscles, and both healthy and T2D human muscles exposed to AICAR, exhibited an increase on glucose transport in the absence of insulin (Bergeron et al 1999, Hayashi et al 1998, Koistinen et al 2003, Miyamoto et al 2007). In addition, the combination of AICAR and insulin promoted an additional glucose transport in muscle and neuronal cells (Shah et al 2011, Fediuc et al 2006, Hayashi et al 1998. However, the effect of AICAR on glucose uptake is lost when α2 or γ3 AMPK subunits are deficient (Barnes et al 2004, Jorgensen et al 2004, Mu et al 2001.…”
Section: Amp-activated Protein Kinase (Ampk)mentioning
confidence: 99%
“…Indirect immunofluorescence for GLUT4myc translocation was carried out on intact cells as described (Kishi et al, 1998). The following steps were performed at 4°C unless indicated otherwise.…”
Section: Glut4myc Translocation Assaymentioning
confidence: 99%
“…GLUT4 protein with an exofacial myc epitope (GLUT4myc) cDNA was constructed by inserting the human c-myc epitope (14 amino acids) into the first ectodomain of GLUT4 and subcloned into the pCXN2 expression vector (Kanai et al, 1993). A clone of L6 skeletal muscle cells isolated for high fusion potential (Mitsumoto et al, 1991) was transfected with pCXN2-GLUT4myc to create a stable cell line, L6-GLUT4myc (L6 myoblasts stably expressing GLUT4myc protein) (Kishi et al, 1998). Constructs for expression of GFP fusion proteins of VAMP2 (V2-GFP) and VAMP3 (V3-GFP) were prepared with the use of the pEGFP-N1 vectors as described (Bajno et al, 2000).…”
Section: Reagents Constructs and Cell Linesmentioning
confidence: 99%